Implementation of Flipped Learning Based on Video Learning to Improve English Speaking Ability - Oya, Abas Oya; Nurfidah, Nurfidah (Lembaga Penelitian dan Pendidikan Mandala, 2023)
The video-based learning model is an effective and enjoyable learning concept for students against laziness in learning and understanding material from writing/textbooks. The use of learning videos will make it easier to understand when delivering lecture material. This learning video was designed directly by researchers based on the material in each lecture. Learning using videos with the application of flipped learning will be very suitable and helpful for the conditions of STKIP Harapan Bima students in learning English. The aim of the research is to improve students' English speaking abilities through video-based learning in a flipped learning approach. This research is Research and Development (R & D) research by adopting the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The methodology used is a mix method (a combination of qualitative and quantitative methods). The instrument used in data collection was a questionnaire which was processed through a validity test. This video-based learning supports the success of the flipped classroom for the Non-English PGSD Study Program because it involves several learning characteristics (a) student-centered learning, (b) an ecosystem to generate learning motivation, and (d) contextual learning experiences.